Settlement of Footings on Compacted and Natural Collapsible Soils upon Loading and Soaking - Rodrigues, Roger Augusto; Prado Soares, Fabio Visnadi; Sanchez, Marcelo (American Society of Civil Engineers (ASCE), 2021)
Collapsible unsaturated soils experience large volumetric compressive deformations upon wetting. Soil collapse is a geotechnical problem that occurs in different regions of the world and profoundly impacts buildings and civil infrastructure constructed on this type of soil, with the associated impact on safety and economy. Compaction is a simple, relatively cheap, and yet effective soil improvement technique that could significantly reduce soil collapsibility. This paper combines laboratory tests, in-situ investigations, and numerical modeling to gain a better understanding of the effect of soil compaction on collapsible-soil settlements upon wetting under field conditions. The finite elements program CODE_BRIGHT was adopted for the numerical simulations of the field tests using model parameters that were previously obtained from independent laboratory experiments. The laboratory campaign comprised suction-controlled oedometer and triaxial tests of the natural and compacted soils considered in this study, as well as permeability and water retention experiments. The numerical simulations show that the proposed approach can model the behavior observed in the in-situ tests involving footing prototypes on collapsible soils subjected to soaking. These analyses also demonstrate that soil compaction is a viable technique to reduce collapsibility in order to meet predefined maximum allowable settlements. Additional analyses were carried out to extend the main findings to other soils and loading conditions. Based on stress-bulb concepts, a method is proposed to reduce settlements in collapsible soils for typical footing operational conditions.
Keywords: Field and laboratory tests; Footing on collapsible soils; Numerical modeling; Unsaturated soils